Can Improving Postoperative Sleep Speed Up Surgical Recovery? - da Silva, Flavia Rodrigues; Guerreiro, Renato de Carvalho; Barreto, Amaury Tavares; Brant, Valdênio Martins; Silva, Andressa; De-Mello, Marco Túlio (Sleep Science, 2024)
Sleep disturbance is common during recovery after surgical procedures and may have an important effect on mortality, and quality of life. Sleep restriction/deprivation, including decreased quantity and continuity, is common in patients who are patients and persons with acute and chronic illnesses. Age, gender, illness, primary sleep disorders, environment, and medical treatment factors are thought to influence sleep throughout the preoperative period, hospitalization, and recovery. Resulting sleep pattern disturbances include decreases in circadian patterning, continuity, duration, and perceived (subjective) sleep quality. This article synthesizes sleep disturbance in patients who have undergone surgery and highlights sleep strategies to improve faster surgical recovery.
Keywords: surgery; sleep; sleep initiation and maintenance disorders